Hong Kong : global China's restive frontier - Lee, Ching Kwan (Cambridge University Press, 2022)
How did Hong Kong transform itself from a 'shoppers' and capitalists' paradise' into a 'city of protests' at the frontline of a global anti-China backlash? CK Lee situates the post-1997 China-Hong Kong contestation in the broader context of 'global China.' Beijing deploys a bundle of power mechanisms - economic statecraft, patron-clientelism, and symbolic domination - around the world, including Hong Kong. This Chinese power project triggers a variety of countermovements from Asia to Africa, ranging from acquiescence and adaptation to appropriation and resistance. In Hong Kong, reactions against the totality of Chinese power have taken the form of eventful protests, which, over two decades, have broadened into a momentous decolonization struggle. More than an ideological conflict between a liberal capitalist democratizing city and its Communist authoritarian sovereign, the Hong Kong story, stunning and singular in its many peculiarities, offers lessons about China as a global force.
Title from publisher's bibliographic system (viewed on 27 Jul 2022).
Keywords: Hong Kong (China) -- Relations -- China.; China -- Relations -- China -- Hong Kong.